Mechanical effect of static loading on endodontically treated teeth restored with fiber‐reinforced posts. Issue 2 (2nd September 2013) - Chieruzzi, Manila; Rallini, Marco; Pagano, Stefano; Eramo, Stefano; D'Errico, Potito; Torre, Luigi; Kenny, José M.
Abstract The aim of this study was to investigate the mechanical behavior of a dental system built up with fiber‐reinforced composite (FRC) endodontic posts with different types of fibers and two cements (the first one used with a primer, the second one without it). Six FRC posts were used. Each system was characterized in terms of structural efficiency under external applied loads similar to masticatory forces. An oblique force was applied and stiffness and maximum load data were obtained. The same test was used for the dentine. The systems were analyzed by scanning electron microscope (SEM) to investigate the surface of the post and inner surface of root canal after failure. The mechanical tests showed that load values in dental systems depend on the post material and used cement. The highest load (281 ± 59 N) was observed for the conical glass fiber posts in the cement without primer. There was a 50 and 85% increase in the maximum load for two of the conical posts with glass fibers and a 229% increase for the carbon fiber posts in the cement without primer as compared with the cement with primer. Moreover, almost all the studied systems showed fracture resistances higher than the typical masticatory loads. The microscopic analysis underlined the good adhesion of the second cement at the interfaces between dentine and post. The mechanical tests confirmed that the strength of the dental systems subjected to masticatory loads was strictly related to the bond at the interface post/cement and cement/dentine. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 384–394, 2014.